2017
DOI: 10.2147/ndt.s139316
|View full text |Cite
|
Sign up to set email alerts
|

De Ritis ratio (AST/ALT) as an independent predictor of poor outcome in patients with acute ischemic stroke

Abstract: PurposeThe aspartate transaminase/alanine transaminase ratio (De Ritis ratio, AAR) was reported to be associated with patients’ prognosis in certain diseases recently. The objective of the current study was to determine the association between the AAR at admission and poor outcome at 3 months in acute ischemic stroke (AIS) patients.Patients and methodsThis retrospective cohort study included patients who experienced their first-ever AIS between June 2015 and March 2016. The primary outcome measure was a poor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…erefore, AAR can be used for the diagnosis and prognosis of various diseases. In addition, the predictive utility of AAR was reported for acute ischemic stroke [41], cardiovascular events, [21] and peripheral arterial occlusive disease [42], where a group with AAR >1.67 had more frequent myocardial infarction, atrial fibrillation, and heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, AAR can be used for the diagnosis and prognosis of various diseases. In addition, the predictive utility of AAR was reported for acute ischemic stroke [41], cardiovascular events, [21] and peripheral arterial occlusive disease [42], where a group with AAR >1.67 had more frequent myocardial infarction, atrial fibrillation, and heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the value of AST/ALT in cardiovascular and cerebrovascular diseases has gradually attracted the consideration of researchers [ 13 , 14 ]. Several studies demonstrated that elevated AST/ALT, assessed at baseline, is an independent risk factor for morbidity and mortality in cardiovascular disease [ 6 , 15 , 16 ]. Since baPWV is also associated with cardiovascular morbidity and mortality, the potential clinical value of this study is that AST/ALT may be used for the assessment of arterial stiffness in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Not only in malignant tumors, the predictive value of DRR in other diseases is also noteworthy. For example, DRR was the independent risk factors of acute ischemic stroke (AIS) and peripheral arterial occlusive disease, as reported by Gao, F. and Rief, P. respectively [22,23] . Rahmani J et al found that high levels of gamma-glutamyl transpeptidase, A Lkaline Phosphatase, AST/ALT were all associated with an increased mortality rate of patients with cardiovascular disease through systematic review and meta-analysis including more than 1 million participants [31] .…”
Section: Relation To Previous Workmentioning
confidence: 63%
“…The distribution of AST is noted in different tissues and organs, which presents with extensive elevation under expose to not only liver damage but other conditions with great need in high metabolic activity, especially for tumor progression [20,21] . In addition to malignant tumors, previous studies also indicated that these biomarkers were also associated with the development and progression of acute ischemic stroke, renal dysfunction, respiratory dysfunction, peripheral arterial occlusive disease [22][23][24][25] . As these diseases are accompanied by abnormalities in cell metabolism, an increase in anaerobic glycolysis tends to cause a disproportionate increase in AST and ALT [26] .…”
Section: Introductionmentioning
confidence: 99%